THE TURNOVER INTENTION IN TELECOMMUNICATION COMPANY: THE IMPORTANCE ROLE OF EFFECTIVE HUMAN RESOURCE PRACTICES AND AFFECTIVE ORGANIZATIONAL COMMITMENTS AS ANTECEDENTS - Saragih, Romat; Luturlean, Bachruddin Saleh; Prasetio, Arif Partono (Jurnal Aplikasi Manajemen, 2020)
Based on the social exchange theory, turnover can be dealt with properly if the company can provide good human resource management and develop employee's emotional attachments. Perceived trust, justice, and fair treatment will develop a positive sense and identification. This empirical study was conducted in Jakarta with 114 telecommunication provider employees working in the finance division. Furthermore, this study examined the relationship between officers' perceptions of effective human resources (HR) practices and employees'turnover mediated by affective commitment. Effective HR practice develops stronger affective commitment which turns to affect their intention to leave. To test hypotheses, we used SPSS 21 with the Macro process. Regression and bootstrap analysis results illustrated that perceived effective HR practice does not significantly affect turnover intention. However, it affected the affective organizational commitment which then influenced the intention to leave. That is affective commitment mediated the relations. HR practitioners should be aware that merely implementing HR practices may not suffice, instead, they should also focus their attention on how the impact on affective commitment when implementing them. It is suggested that further study needs to focus on other independent variables such as work-life balance, reward satisfaction, co-workers support, and career development to tackle turnover problems. Consideration to use longitudinal data will also increase accuracy. This study aims to contribute to the HR and organizational behavior literature by testing the effect of HR practice and affective commitment as an antecedent of turnover intention using social exchange background.